2015
DOI: 10.1111/febs.13413
|View full text |Cite
|
Sign up to set email alerts
|

A kinetic model for the prevalence of mono‐ over poly‐pupylation

Abstract: Bacteria belonging to the phyla Actinobacteria and Nitrospira possess proteasome cores homologous to the eukaryotic 20S proteasome particle. In these bacteria, the cytoplasmic signal for proteasomal degradation is a small protein termed Pup (prokaryotic ubiquitin‐like protein). PafA, the only known Pup ligase, conjugates Pup to lysine side chains of target proteins. In contrast to the eukaryotic ubiquitin‐proteasome system, where poly‐ubiquitin chains are the principal tags for proteasomal degradation, mono‐Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…This notion is supported by the fact that many M. smegmatis and M. tuberculosis HMW proteins were not detected in the pupylomes of these species (5,9,15,16). It is further supported by the fact that a good substrate can be converted into a poor substrate by mutagenesis of its target lysine (10,27), a mutation that hardly affects its size and the accessibility of other lysines in the protein.…”
Section: Controlling Dop Levels Balances Deamidation With Depupylationmentioning
confidence: 92%
See 3 more Smart Citations
“…This notion is supported by the fact that many M. smegmatis and M. tuberculosis HMW proteins were not detected in the pupylomes of these species (5,9,15,16). It is further supported by the fact that a good substrate can be converted into a poor substrate by mutagenesis of its target lysine (10,27), a mutation that hardly affects its size and the accessibility of other lysines in the protein.…”
Section: Controlling Dop Levels Balances Deamidation With Depupylationmentioning
confidence: 92%
“…All proteins used in this study were recombinant M. smegmatis proteins, with the exception of Ac-Dop. PafA, Pup, and PanB were purified as described by Ofer et al (34), Dop variants and Pup-Fl were purified as described by Hecht and Gur (24), and IdeR, pupylated PanB, and pupylated IdeR were purified as described by Regev et al (10). The M. smegmatis pupylome was purified as described in Elharar et al (5).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…An in vitro study showed for two known pupylation substrates (IdeR and PanB) that poly-pupylation, when it occurs, proceeds via sequential addition of Pup to a growing Pup chain on the substrate rather than by attaching an existing poly-Pup [76]. The study further concludes that in case the affinity for mono-pupylated substrate is similar to unpupylated target as for IdeR, polypupylation occurs along with monopupylation, whereas for much higher affinity of unpupylated target, as is the case for PanB, monopupylation is preferred.…”
Section: Reaction Mechanism Of Pupylation and Depupylationmentioning
confidence: 99%